Blast Response of Slabs in ReinforcedConcrete Buildings - YAZICI, GÖKHAN (My University, 2018)
This study presents the response of reinforced concrete slabs in building structures exposed to blast loads. The mid-span displacements, support rotations, and damage patterns were investigated for a varying charge mass located underneath the slab. Detonations were simulated using the airblast-loading functions available in the explicit solver of LS-Dyna. The reinforcements of the slab were modeled by using line elements inserted into the volumetric finite-element mesh of the concrete material. The effects of support conditions on the slab response were evaluated. Results from the numerical study showed that the slab failed first at the supports before the midspan region disintegrated due to rebar ruptures. Therefore, the strengthening of the support region plays a crucial role in the blast response of the slab. Suggestions for blast upgrading of reinforced concrete slabs were summarized.